Clinical Significance of Blastocystis Sp. among Children with Leukemia - khalil, Zainab Khalid (AL-Kindy College Medical Journal, 2019)
Background: Blastocystis spp. distributes world widely and the genus Blastocystis include many subtypes that are isolated from human intestinal tract. It is considered the most common parasite detected in human being.Objectives: To evaluate the incidence of Blastocystis spp. among leukemic children, to find out its association with the presence of symptoms (diarrhea and abdominal pain), and to assess the efficacy of different staining methods in detection of Blastocystis spp. Type of the study: cross-sectional study.Method: 103 children were enrolled in this study, 53 leukemic patients and 50 healthy controls. The study was performed during the period between January and June 2014, in Oncology department of Ibn Al-Atheer teaching hospital in Mosul city. Three consecutive samples were taken from each child and a thorough history was taken from them. The samples then treated with 3 stains, iodine, iron hematoxylin, and trichrome.The data was analyzed using minitab version 17, Fischer’s exact test, Two-proportions test, and Correlation test. The results were considered statistically significant with P-value